2010
DOI: 10.1021/jp107907s
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Binary Blends of Diblock Copolymers

Abstract: The phase behavior of binary blends of a long symmetric AB diblock copolymer and a short asymmetric AB diblock copolymer is studied using the self-consistent mean-field theory. The investigation focuses on blends with different short diblocks by constructing phase diagrams over the whole blending compositions and a large segregation regime. The influences of the chain length ratio (R) of the long and short diblock copolymers on their miscibility and on the stability of various ordered structures are explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 37 publications
8
44
0
Order By: Relevance
“…The most interesting result of the AFM investigation is the absence of macrophase separation. According to both experimental and theoretical studies, macro­phase separation is expected for φ β = 0.3–0.7 for the blends studied here. Obviously, AFM only monitors the near‐surface structures, which may differ from the ones within the thin films.…”
Section: Resultssupporting
confidence: 63%
“…The most interesting result of the AFM investigation is the absence of macrophase separation. According to both experimental and theoretical studies, macro­phase separation is expected for φ β = 0.3–0.7 for the blends studied here. Obviously, AFM only monitors the near‐surface structures, which may differ from the ones within the thin films.…”
Section: Resultssupporting
confidence: 63%
“…It has been shown before, that this ratio is not only essential for whether microphase or macrophase separation takes place, but it has also control over the resulting morphology. Wu et al . have demonstrated with the use of the SCFT how the phase diagram for binary blends of diblock copolymers dramatically changes when the chain length ratio R is altered.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown before, that this ratio is not only essential for whether microphase or macrophase separation takes place, [68,69] but it has also control over the resulting morphology. Wu et al [70] have demonstrated with the use of the SCFT how the phase diagram for binary blends of diblock copolymers dramatically changes when the chain length ratio R is altered. In our work, we have maintained this ratio at a nearly constant value but they are interchanged for both blend series: in series A the chain of SIM is 1.8 times longer than the chain of ISM and in series B the chain of ISM is 1.9 times longer than the chain of SIM.…”
Section: Wwwadvancedsciencenewscom Wwwmcp-journaldementioning
confidence: 99%
“…For example, Matsen [ 29 ] calculated the phase separation between two symmetric diblock blends and found that macrophase separation occurs if the chain length ratio of long diblock to short diblock is larger than 5, and the volume fraction of short copolymer larger than 0.2. Another interesting simulation study by Wu et al in 2010 [ 30 ] concerned the phase behavior of binary blends of a long symmetric AB diblock copolymer and a short asymmetric AB, where macrophase separation occurred when the chain length ratio was large enough (≈5.3).…”
Section: From Monomodal To Multimodal Dispersity Using Blends Of Blocmentioning
confidence: 99%